The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3747/pdi.2017.00287
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prevention of Peritoneal Dialysis-Related Peritonitis

Abstract: Background Peritonitis is a major complication and the main cause of peritoneal dialysis (PD) failure. The aim of the present study was to evaluate peritonitis risk factors and its prevention with a new peritoneal educational program (NPEP). Methods We performed a retrospective analysis of a cohort of chronic PD patients, older than 16 years, who began PD in the period 1 January 1999 to 31 December 2015 at a Uruguayan PD center, with follow-up until 31 December 2016. Results The population included 222 cases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
52
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(63 citation statements)
references
References 39 publications
3
52
0
4
Order By: Relevance
“…Predictive value for peritonitis of serum prealbumin, OH is also evident when we followed-up 3 years CAPD patients by Kaplan-Meier analysis (Figure 2,3). There are some previous reports about predictive factors of PD-related peritonitis in CAPD patients [19,21,22]. Gadola L. et al [19] con rmed that multidisciplinary peritoneal educational program improved peritonitis rates, independently of other risk factors.…”
Section: Factors Predict Peritonitismentioning
confidence: 89%
See 2 more Smart Citations
“…Predictive value for peritonitis of serum prealbumin, OH is also evident when we followed-up 3 years CAPD patients by Kaplan-Meier analysis (Figure 2,3). There are some previous reports about predictive factors of PD-related peritonitis in CAPD patients [19,21,22]. Gadola L. et al [19] con rmed that multidisciplinary peritoneal educational program improved peritonitis rates, independently of other risk factors.…”
Section: Factors Predict Peritonitismentioning
confidence: 89%
“…There are some previous reports about predictive factors of PD-related peritonitis in CAPD patients [19,21,22]. Gadola L. et al [19] con rmed that multidisciplinary peritoneal educational program improved peritonitis rates, independently of other risk factors. Okayama M. et al found aging is an important risk factor for peritoneal dialysis-associated peritonitis [21].…”
Section: Factors Predict Peritonitismentioning
confidence: 89%
See 1 more Smart Citation
“…There are some previous reports about predictive factors of PDrelated peritonitis in CAPD patients [18,20,21]. Gadola L. et al [18] con rmed that multidisciplinary peritoneal educational program improved peritonitis rates, independently of other risk factors. Okayama M. et al found aging is an important risk factor for peritoneal dialysis-associated peritonitis [20].…”
Section: Factors Predict Peritonitismentioning
confidence: 90%
“…Ye H. et al [5] conducted a study with 1321 PD patients following-up 5 years, the ratio of peritonitis was 28.16% (372/1321 patients), in which in the rst year of PD initiation, 169 (13%) patients had experienced episodes of peritonitis, and the proportion of patients with peritonitis uctuated from 8-13% in the subsequent years. Gadola L. et al [18] surveyed the rate of peritonitis in 222 PD patients following-up 6 years, the result showed 95 patients suffered 1 or more episodes of peritonitis (42.79%). In children, the ratio of peritonitis was 25.45% in Ponce's study with 7 years follow-up (125 rst episodes of peritonitis in 491 children PD patients) [19].…”
Section: Prevalence Peritonitismentioning
confidence: 99%